2020
DOI: 10.1177/1350650120935007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of V-shape protruded and dimple textured on the load-carrying capacity and coefficient of friction of hydrodynamic journal bearing: A comparative numerical study

Abstract: The present comparative numerical study is between V-shape protruded, dimple textured, and untextured bearing. The performance parameters in terms of the load-carrying capacity and coefficient of friction are computed by solving governing Reynold’s equation of the lubricant fluid flow. The governing equation is solved by the finite element method by assuming that the fluid is Newtonian and isoviscous in nature. The effect of eccentricity ratios, texture distribution, texture heights, and texture depths are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Lately, Filgueira Filho et al [20] experimentally analyzed the performances of textured journal bearings with chevron, saw tooth, oblong dimple, and aligned dimple and found that the chevron textured journal bearing exhibited smaller eccentricity under reasonable texture geometrical parameters. Besides, some researchers [21][22][23] also analyzed the influence of protruded and dimple textures on the loadcarrying capacity and friction of journal bearings and compared the results with that of smooth journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Filgueira Filho et al [20] experimentally analyzed the performances of textured journal bearings with chevron, saw tooth, oblong dimple, and aligned dimple and found that the chevron textured journal bearing exhibited smaller eccentricity under reasonable texture geometrical parameters. Besides, some researchers [21][22][23] also analyzed the influence of protruded and dimple textures on the loadcarrying capacity and friction of journal bearings and compared the results with that of smooth journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…As partial texturing improve the performance of the bearing as reported by various researchers, [28][29][30][31][32] hence the static performance parameters defined by bearing load capacity and friction coefficient are calculated for bearings with partial surface waviness in five different regions, namely 0-360 , 0-180 , 180-360 , 185-288 , and 288-339 , as illustrated in Figure 3a-d in circumferential, axial, and both directions. 31,32 The comparison of performance parameters has been done for different regions at various wavenumbers and wave amplitudes to get optimal results. The simulated results of partial surface waviness improve the performance of the bearing and also reduce the cost of manufacturing bearings with partial surface waviness as compared to full surface waviness by using methods such as selective laser melting (SLM), selective laser sintering (SLS), additive manufacturing process, and so forth.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, some research looked into the effect of other surface morphologies of the bearing and journal on bearing performance. Khatri and Sharma, 28 Tala-Ighil and Fillon, 29 Uddin and Liu, 30 and, Sharma et al 31,32 investigated the effect of different texturing geometries and their placement in different regions on bearing performance. Kango et al 33 examined the effects of spherical texture and microgrooving on the friction coefficient and average temperature of journal bearings at low and high eccentricity ratios and found that the micro-grooving significantly lowers the friction coefficient and increases the average temperature in comparison to spherical texture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng et al (2021) pointed that a critical compound texture depth can improve the critical speed of bearing-rotor system. Sharma et al (2021) compared the bearing performance between V-shape protruded, dimple textured and untextured bearing. Hingawe and Bhore (2020) analyzed various texture bottom profiles: flat, triangle and curved for improving the hydrodynamic performance of moving parts.…”
Section: Introductionmentioning
confidence: 99%